2022
DOI: 10.1108/jm2-06-2021-0145
|View full text |Cite
|
Sign up to set email alerts
|

A framework for assessment of critical factor for circular economy practice implementation

Abstract: Purpose Consumers, governments and regulatory agencies are concerned about the social and environmental aspect that pushes firms to move towards the circular economy. The transformation of the existing linear model into a circular model depends on several circular economy practices. Therefore, the purpose of this study is to identify and analyse the critical factors that are responsible for the adoption of circular practices. Design/methodology/approach In total, 15 critical factors are identified through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…In the study's second phase, the identified barriers are prioritised using a well-known MCDM method named the best-worst method BIJ 30,10 (BWM). Several other methods, such as AHP, ANP, WASPAS and DANP are also used to prioritise the barriers (Khan et al, 2020;Hossain and Thakur, 2020;Singh et al, 2022). BWM has some advantages over these methods, requiring fewer pairwise comparisons (Rezaei, 2015(Rezaei, , 2016Guo and Zhao, 2017); as the BWM only compares the barriers concerning the most significant barriers (best) and the least significant barriers (worst) with other barriers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study's second phase, the identified barriers are prioritised using a well-known MCDM method named the best-worst method BIJ 30,10 (BWM). Several other methods, such as AHP, ANP, WASPAS and DANP are also used to prioritise the barriers (Khan et al, 2020;Hossain and Thakur, 2020;Singh et al, 2022). BWM has some advantages over these methods, requiring fewer pairwise comparisons (Rezaei, 2015(Rezaei, , 2016Guo and Zhao, 2017); as the BWM only compares the barriers concerning the most significant barriers (best) and the least significant barriers (worst) with other barriers.…”
Section: Methodsmentioning
confidence: 99%
“…Several other methods, such as AHP, ANP, WASPAS and DANP are also used to prioritise the barriers (Khan et al. , 2020; Hossain and Thakur, 2020; Singh et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Internal drivers include for example organizational drivers, resource availability and optimization drivers, financial drivers, and product design and process development, all of which support the implementation of CE [ 31 ]. Organizational drivers may include factors such as good leadership, design strategies, innovation, research and development, and organizational infrastructure [ 32 , 33 ]. While internal drivers are factors that impel CE practices from inside an organization, external drivers on the other hand are the factors that drive CE practices from outside of an organization, including legislative and economic factors.…”
Section: Transition To the Circular Economymentioning
confidence: 99%
“…The increase in the related environmental problems [21][22][23] actualizes not only the need to develop a green mining strategy [24], green technologies for mineral enrichment [25], involving other sustainable technologies [26] but also a transition to a sustainable use of mineral resources based on circular economy models [27][28][29]. A circular economy implies the closure of resource flows without forming associated wastes [30][31][32]. This direction is the dominant tool in developing national strategies used for sustainable development all over the world [33].…”
Section: Introductionmentioning
confidence: 99%